PERMOHONAN DISPENSASI NIKAH DI PENGADILAN AGAMA INDRAMAYU DALAM PERSPEKTIF HUKUM DAN SOSIOLOGI HUKUM - Eko Syukri Mulyadi (SUPREMASI HUKUM, 2023)
This study uses a data analysis model in which qualitative data analysis is followed by data collection from the Indramayu Religious Court and other laws to support data analysis. This method involves collecting data from primary and secondary sources for research. The data were tested without using statistical formulas or mathematical models, and the findings will be presented in a descriptive analysis. In addition, deductive conclusions are drawn in response to the questions being investigated. The granting of marital dispensation to children who are to be married off under the age is one example of a legal decision that will undoubtedly have a direct impact from a sociological and legal perspective. The minimum age a person may marry is not explicitly stated in the Qur'an. In contrast to the majority of scholars, such as Ibn Subrumah, Bakar Al-A'sham, and Utsmaan Al-Batt, who stated: that young man is not legally married, they cannot marry until they reach puberty and have clear consent from their parents. Keywords: Marriage Dispensation; Religious courts; Law; Legal Sociology.